Role of Placement of Wet Gauze Versus Dry Gauze After Extraction of Molars in Prevention of Dry Socket - Zoina; Hammad, Jahangir; Alam, Maqbool; Khan, Sidra; Jan, Rahim; Wahed, Abdal (Indus Journal of Bioscience Research, 2025)
Background: One of the most frequent outpatient treatments is dental extraction, and there are serious risks of post-extraction problems such bleeding and dry socket (alveolar osteitis). The type of gauze employed and other aspects of the extraction site treatment are crucial for the healing and retention of the clot. Objective: The purpose of this study is to evaluate pain levels, healing progress, and patient satisfaction while comparing the efficacy of wet and dry gauze in preventing dry socket after molar extractions. Methods: Two groups—wet gauze (Group A) and dry gauze (Group B)—were randomly assigned to 200 patients having molar extractions. On the third and seventh postoperative days, the incidence of dry socket, visual analog scale discomfort, wound healing, and general patient satisfaction were tracked. Results: In contrast to the dry gauze group, which saw a rate of 15% on Day 3 and 21% on Day 7, the wet gauze group experienced a much lower incidence of dry socket (4% on Day 3 and 6% on Day 7). The moist gauze group saw consistently reduced pain levels and far better healing; on Day 7, 94% of wet gauze patients had satisfactory healing, compared to 75% of the dry gauze group. Additionally, the wet gauze group had higher patient satisfaction. Conclusion: After molar extractions, wet gauze greatly lowers the danger of dry socket, lessens pain, speeds up healing, and improves patient comfort. The recommended method for post-extraction care should be wet gauze.